A systematic review on environmentally friendly hydrogen production methods: comparative analysis of reactor technologies for optimal efficiency and sustainability - Hamid, Aisha; Deris, Raja Razuan Raja; Shaffee, Siti Nur Amira; Hin, Taufiq Yap Yun; Ametefe, Divine Senanu; Ibrahim, Mohd Lokman (Elsevier, 2025)
The transition to a hydrogen-based energy system is increasingly viewed as vital for achieving global sustainability and decarbonization goals. This systematic literature review (SLR) critically examines 37 peer-reviewed studies (2018–Q2 2024) on key hydrogen production methods: biomass gasification, auto-thermal reforming (ATR), photochemical water splitting, water electrolysis, and steam reforming. These technologies, while diverse in operational principles and efficiency, converge on the goal of delivering low-carbon hydrogen. Steam reforming remains the most commercially mature, yet it is constrained by high energy demands and catalyst degradation. Biomass gasification emerges as a renewable option, though hampered by cost and technical complexity. ATR offers improved energy efficiency but requires stringent process control. Photochemical water splitting, though promising in its solar-driven mechanism, is hindered by low conversion efficiency and material limitations. Water electrolysis, especially when powered by renewables, delivers high-purity hydrogen, albeit at elevated operational costs. The findings underscore that no single method can universally meet all economic, environmental, and technological criteria. Instead, context-specific hybridization and integration with renewable sources appear most viable. This review emphasizes the need for continued research in advanced catalysts, cost-effective materials, and scalable system designs. It also calls for cross-sectoral collaboration to tailor hydrogen strategies to local resource conditions and energy demands. By articulating the strengths, limitations, and future directions of current hydrogen production pathways, this study contributes to the evolving discourse on sustainable energy and supports informed decision-making toward a resilient, low-carbon future.